2015
DOI: 10.3390/w7062542
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Field Test to Evaluate the Maintenance Requirements of Permeable Interlocking Concrete Pavements

Abstract: Adequate infiltration through Permeable Interlocking Concrete Pavements (PICPs) is critical to their hydraulic and stormwater treatment performance. Infiltration is affected by clogging caused by the trapping of fines in the PICP surface, which, over time, reduces treatment performance. Clogging can be reduced by periodic maintenance such as vacuum sweeping and/or pressure washing. Maintenance requirements can be indicated by measuring reduced infiltration rates. This paper compared infiltration results using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 20 publications
3
32
3
Order By: Relevance
“…The Shapiro-Wilk test was conducted on the pooled data where all the infiltration tests conducted on the surface, regardless of location, were lumped into one data set as done in similar studies [18,25,29]. Pooled data sets were created for each ring size, for each surface and for each type of test method (either ASTM or falling head).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Shapiro-Wilk test was conducted on the pooled data where all the infiltration tests conducted on the surface, regardless of location, were lumped into one data set as done in similar studies [18,25,29]. Pooled data sets were created for each ring size, for each surface and for each type of test method (either ASTM or falling head).…”
Section: Methodsmentioning
confidence: 99%
“…Since the introduction of this standard, a number of studies evaluating the accuracy of the ASTM standard tests, or comparing them to other methods for determining SIR, can be found in the literature [16,[24][25][26][27][28][29]. These comparisons are useful not only in judging the general use of such a method, but the precision by which it can provide a measure of SIR because of modeling needs and maintenance requirements [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that the most accurate results were associated with the falling head full-scale testing method. Recently, a stormwater infiltration field test (SWIFT) method was developed in Australia [26] as a fast and inexpensive method for permeable pavement assessment. The SWIFT method was compared with the single-ring infiltrometer test (ASTM C1781M-14a) method and a good agreement was found between these methods.…”
Section: Infiltration Methodsmentioning
confidence: 99%
“…Categories of PICP pavement clogging and associated infiltration rates are listed in Table 5. [152] These values could be used by engineers as a guide to assess clogging.…”
Section: Cloggingmentioning
confidence: 99%